2008
DOI: 10.1039/b712175j
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle superlattices

Abstract: Ordered metal nanoparticle assemblies--superlattices--have captivated and stirred the imagination of scientists and engineers alike and promise great prospect for future technologies. This potential though will greatly be determined by the understanding and control that can be exerted on the assembling processes. This tutorial review presents a brief account of the factors that govern the formation of superlattices and then presents several examples of gold nanoparticle superlattices that are distinguished by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
154
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(161 citation statements)
references
References 67 publications
3
154
0
4
Order By: Relevance
“…[24,59] Dem Bauprinzip der Opale folgend zielt die Materialsynthese auf eine kontrollierte "Kristallisation" monodisperser NPs mit hohem Brechungsindex zu so genannten photonischen Kristallen, die als Lichtwellenleiter, optische Speicher, schwellenlose Laser oder für die optische Datenverarbeitung hochrelevant sind. [60] ¾hnlich zur elektronischen Bandlücke der Halbleiter beobachtet man hier eine optische Bandlücke, d. h. elektromagnetische Wellen, die in einem bestimmten Wellenlängen-bereich in den photonischen Kristall nicht eindringen können. Technisch interessant sind photonische Kristalle insbesondere, wenn eine vollständige optische Bandlücke (d. h. 100 % Reflexion) vorliegt, wofür ein Brechungsindexunterschied > 2.8 erforderlich ist (z.…”
Section: Konzepte Zur Synthese Von Nanopartikelnunclassified
See 1 more Smart Citation
“…[24,59] Dem Bauprinzip der Opale folgend zielt die Materialsynthese auf eine kontrollierte "Kristallisation" monodisperser NPs mit hohem Brechungsindex zu so genannten photonischen Kristallen, die als Lichtwellenleiter, optische Speicher, schwellenlose Laser oder für die optische Datenverarbeitung hochrelevant sind. [60] ¾hnlich zur elektronischen Bandlücke der Halbleiter beobachtet man hier eine optische Bandlücke, d. h. elektromagnetische Wellen, die in einem bestimmten Wellenlängen-bereich in den photonischen Kristall nicht eindringen können. Technisch interessant sind photonische Kristalle insbesondere, wenn eine vollständige optische Bandlücke (d. h. 100 % Reflexion) vorliegt, wofür ein Brechungsindexunterschied > 2.8 erforderlich ist (z.…”
Section: Konzepte Zur Synthese Von Nanopartikelnunclassified
“…[294] Die Kristallisation von NPs mit hohem Brechungsindex hatten wir unter dem Begriff der photonischen Kristalle bereits in Abschnitt 3.2 besprochen. [60] Nanopartikel Angewandte Chemie mente (z. B.…”
Section: Veredlung Von Bulkwerkstoffenunclassified
“…To date, a few reviews have discussed nanoparticle superlattices,1, 2, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34 however, a dedicated review emphasizing the important roles of soft ligands has not yet reported to the best of our knowledge. We therefore are motivated to cover the recent advances in nanoparticle superlattices from viewpoint of soft ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Gold has been studied most extensively, and it has been interesting to observe that the results can be separated into two categories: (1) small nanocrystals, better termed clusters of gold atoms, such as Au 24 , 13 Au 25 , [14][15][16][17][18] Au 38 , 11,19 Au 102 , 20 Au 130 , 21 Au 144 , 22 Au 225 , 23 and a few others; (2) gold nanoparticles of 3 -5 nm (1000 to 4000 atoms) [1][2][3][4][5] and sometimes 9 -10 nm. 24 For both categories it has been shown that there are clearly numerous examples of size focusing under apparent thermodynamic control.…”
Section: Introductionmentioning
confidence: 99%